Using personal narrative to promote person-centered values in aging, dementia, and caregiving - Merrilees, Jennifer; Mayotte, Cliff; Vong, Erin; Matice, Mindy; Prioleau, Caroline (Frontiers in Neurology, 2023)
Personal narrative is a powerful way to include people in their care and to understand their values that drive their needs. In this paper, we describe a program designed to teach oral history to clinicians and trainees in the field of aging, dementia and caregiving. The training uses empathic listening, open-ended interviewing, and the discovery of individual values and experience to breakdown stigma and preconceptions of what it means to age with cognitive impairment. Sharing these stories of aging, dementia, and caregiving becomes an important tool to break down stereotypes, promote person-centered care, and advocate for the unheard. The profound impact of the oral history process is felt by the narrator, the interviewer and the listener. Human beings are wired for stories, and oral history taps into that power to connect us and provide better care through better understanding.